FUNCTIONAL AND PASTING PROPERTIES OF FLOUR PRODUCED FROM POTATO (SOLANUM TUBEROSUM) TUBER STORED UNDER DIFFERENT CONDITIONS - Okache, Thomas Akobi; Karim, Olayinka Ramota; Dauda, Adegbola Oladele; Edem, Victor Ephraim; Kamaldeen, Oladimeji Salaudeen (FUDMA JOURNAL OF SCIENCES, 2025)
Potato is a starchy tuber, consumed as staple in most parts of the world. Potato storage is essential in preserving tuber quality to ensure its suitability for culinary purposes. This study aimed to evaluate the impact of four storage methods consisting of pit storage (PS), room storage (RS), metal-in-block evaporative cooling system (EC), and charcoal cooling chamber (CC) on the physicochemical properties of potato flour. The objectives were to assess the functional and pasting properties of flour produced from stored potato. The study employed a randomized complete block design involving these storage methods. Samples from the various storage methods each containing 4.8-5.0 kg of potato were analyzed fortnightly for eight weeks. The physicochemical properties of the flour were assessed, data obtained were subjected to analysis of variance, and means were separated using Duncan multiple range test. The findings of this study were that: The functional properties of potato flour were significantly affected (p<0.05) by storage methods as parameter varied in their bulk density (0.76-0.87 g/ml), water absorption capacity (2.29-2.68ml/g), and swelling capacity (2.60-3.88 ml/g). The pasting properties showed variations in paste viscosity as values ranged from 2486.50-4531.00 cP, while pasting time and temperature were 4.30-5.77 minutes and 71.70-74.63 °C, respectively. The study concluded that the physicochemical properties of potato flour were significantly influenced by the different storage methods, and the EC and CC were the most effective methods for potato storage. The study, therefore recommended CC for adoption based on its affordability.